Sepsis associated with acute lung injury over the period 2012–2021: a bibliometric analysis - Liang, Guibin; Wang, Wenhua; He, Zhihui (Frontiers in Physiology, 2023)
Background: Sepsis associated with acute lung injury (ALI) is a common acute and severe disease with severe socioeconomic burden. The aim of this study is to explore the literatures of sepsis associated with ALI from a bibliometric perspective. Methods: Articles and reviews related to sepsis associated with ALI published from 2012 to 2021 in the Web of Science Core Collection were retrieved. Countries, affiliations, journals, authors, references, co-citation and keyword analysis in this field were visually analyzed using WOS citation reports, bibliometric.com, CtieSpace and VOSviewer software. Results: Over the last decade (2012-2021), marked progress has been made in the area of sepsis associated with ALI research. 836 papers were enrolled in this study. China accounts for the most contributors. Articles from the United States has the highest average cited. Shanghai Jiao Tong University, University of California System and Huazhong University of Science Technology were the main contributing institutions. Articles in International Immunopharmacology, Inflammation, Shock and Critical Care were cited the most. Matthay MA and Ware LB were the main contributors to this field. Inflammation and NF-κB have always been the focus of sepsis associated with ALI related research, and programmed cell death (including apoptosis, necroptosis and pyroptosis) may be the important direction of future research. Conclusions: Research on the sepsis associated with ALI is flourishing. The research on programmed cell death is a hot spot and may be a promising research field in the coming years.